IMPLEMENTASI PORTAL WEBSITE PEMETAAN DAN INFORMASI PERGURUAN TINGGI - Syaifudin, Yan Watequlis (DINAMIKA DOTCOM, 2017)
Higher Education is one of the national educational instruments that become the center of the organization and development of science. In this global era, the growth of public and private universities is increasing. There are approximately 400 state and private universities in East Java. It makes it difficult for students to choose the right University for their education, because of the many universities in East Java and the lack of university information. In addition, people are also difficult to find the location of state and private universities. This research developed a website for mapping and searching of state and private universities. From the information search features, user can obtain information of the university in the form of address, facility, faculty, department and study program. So that information can be used as a reference for students to choose which universities are as expected. In addition, this system provides additional features in the form of university location search.Keywords : university, map, location, accreditaition, website